Target Product Profile (TPP) for Chagas Disease Point-of-Care Diagnosis and Assessment of Response to Treatment - Porrás, Analía I. (2015)
Chagas disease, or American trypanosomiasis, affects 8 million people, largely in Latin America, where it is endemic in all countries. With an overall estimate of 65 million people at risk of contracting the disease, 28,000 new cases every year, and 12,000 deaths annually, Chagas disease is the most important parasitic disease in the Americas [1]. In addition, nonendemic countries such as the United States [2,3], Canada [4], Germany [5], Italy [6], Spain [7,8], Switzerland [9,10], and France [11] have experienced the occurrence of Trypanosoma cruzi?infected and Chagas disease cases; the majority of these cases are among immigrants coming from endemic Latin American countries [12]. Like other neglected tropical diseases (NTDs), Chagas disease affects mostly poor populations with limited access to health services. Vector transmission is associated with poor housing in periurban and rural areas. After infection, the disease is characterized by an acute phase, usually asymptomatic, which evolves in 20%?30% of the patients to a chronic disabling cardiac and/or digestive clinical form. The remaining infected individuals evolve to a chronic asymptomatic but infective clinical phase [13]. Reactivation of chronic Chagas disease may occur associated with comorbidities such as HIV/AIDS, organ transplants, or immunosuppressive therapy.